Imaging molecular interactions in cells by dynamic and static fluorescence anisotropy (rFLIM and emFRET). (1st October 2003) - Lidke, D.S.; Nagy, P.; Barisas, B.G.; Heintzmann, R.; Post, J.N.; Lidke, K.A.; Clayton, A.H.A.; Arndt-Jovin, D.J.; Jovin, T.M.
Abstract : We report the implementation and exploitation of fluorescence polarization measurements, in the form of anisotropy fluorescence lifetime imaging microscopy (rFLIM) and energy migration Förster resonance energy transfer (emFRET) modalities, for wide-field, confocal laser-scanning microscopy and flow cytometry of cells. These methods permit the assessment of rotational motion, association and proximity of cellular proteins in vivo . They are particularly applicable to probes generated by fusions of visible fluorescence proteins, as exemplified by studies of the erbB receptor tyrosine kinases involved in growth-factor-mediated signal transduction.